Projeto e desenvolvimento de um sistema intercambiável para inspeção em dutos de petróleo e gás - Barroso, Fábio de Andrade (2011)
The design and development of an automated system for inspection of weld in pipelines main objective to ensure portability in areas of difficult access, improved detectability of errors, accurate reports, scan speed, easy handling and greater flexibility for different configurations in diameter and thickness. From the geometry of the duct, the system is capable of circumferential and longitudinal movements in order to scan the entire surface of the pipeline being inspected. The system consists of two DC motors, gears, a programmable logic controller and a graphical interface to show the maintence of inspection process. The project is based on an interchargeable external gear that rotates and supports the transducers, driven by other gear. Another engine generates the longitudinal movement of the system mensuring that the entire surface of the pipe to be inspected. Experimental tests have demonstrated the effectiveness and applicability of the developed system.